Omega-3 Fatty Acids and Balanced Gut Microbiota on Chronic Inflammatory Diseases: A Close Look at Ulcerative Colitis and Rheumatoid Arthritis Pathogenesis - Zorgetto-Pinheiro, Verônica Assalin; Machate, David Johane; Figueiredo, Priscila Silva; Marcelino, Gabriela; Hiane, Priscila Aiko; Pott, Arnildo; Guimarães, Rita de Cássia Avellaneda; Bogo, Danielle (Journal of medicinal food, 2022)
The aim of this article was to review experimental and clinical studies regarding the use of omega-3 fatty acids on the prevention and control of chronic inflammatory diseases with autoimmune background through the gut microbiota modulation. For this, natural omega-3 sources are presented emphasizing the importance of a healthy diet for the body's homeostasis and the enzymatic processes that these fatty acids go through once inside the body. The pathogenesis of ulcerative colitis and rheumatoid arthritis are revisited under the light of the gut microbiota dysbiosis approach and how those fatty acids are able to prevent and control these two pathological conditions that are responsible for the global chronic burden and functional disability and life-threatening comorbidities if not treated properly. As a matter of reflection, as we are living a pandemic crisis owing to COVID-19 infection, we present the potential of omega-3 in preventing a poor prognosis once they contribute to balancing the immune system modulation the inflammatory process.